Dampak Penetapan Tarif Impor Kedelai di Indonesia dengan Analisis Keseimbangan Parsial - Bayu, Aunaya (Pusat Pendidikan dan Pelatihan Aparatur Perdagangan, 2024)
Soybean is one of strategic foods in Indonesia, with their processed products widely consumed by the population. However, domestic soybean production is currently low, leading to a reliance on imported soybean to meet domestic demand. One form of government intervention to regulate soybean imports is to set soybean import tariffs. The Indonesian government has set a target for food self-sufficiency, including soybean. However, low import tariffs in recent years have had the opposite effect, weakening domestic efforts to increase soybean production and facilitating the flow of soybean imports. This study aims to analyze the impact of soybean import tariffs in Indonesia. The analytical method used is partial equilibrium to calculate the impact of import tariffs on the volume of soybean imports and other economic performance. This study uses basic data on world soybean prices, exchange rate, soybean import volume, domestic soybean production, soybean consumption, and soybean import tariff in 2022. The simulation results show that the liberalization of soybean import tariff results in an increase in soybean import volume and benefits the consumers, but harms soybean producers. On the contrary, the implementation of soybean import tariffs of 5% and 10% results in a decrease in the volume of soybean imports and benefits soybean producers, but harms the consumers.